Principal's managerial strategy in strengthening teacher performance at elementary school - Deli Ema Susana; Niswanto Niswanto; Nasir Usman (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
Low teacher performance in elementary schools is often related to weak managerial practices of principals, particularly in planning, supervision, and communication. Challenges such as assigning teachers who do not match their competencies and ineffective coordination contribute to the deterioration of teaching quality. This study aims to analyze principals' managerial strategies in improving teacher performance, focusing on aspects of program planning, instructional supervision, and leadership communication. This study uses a qualitative descriptive approach with data collection techniques through observation, in-depth interviews, and documentation studies. Research informants included principals, teachers, vice principals, and supervisors from three public elementary schools in the Pisang Cluster, Meuraxa District, Banda Aceh. Data were analyzed using the Miles and Huberman interactive model through the stages of data reduction, data presentation, and conclusion drawing. The results show that principals implement strategies to improve teacher performance through training programs, regular supervision, open dialogue, and teacher involvement in decision-making. Key supporting factors include the availability of learning facilities and conducive communication support. This study contributes to the development of educational leadership practices based on structured and contextual managerial strategies. The implication is that improving the managerial capacity of school principals needs to be a primary focus in strengthening the quality of teaching at the elementary school level.